2016
DOI: 10.1136/annrheumdis-2015-208562
|View full text |Cite
|
Sign up to set email alerts
|

Sifalimumab, an anti-interferon-α monoclonal antibody, in moderate to severe systemic lupus erythematosus: a randomised, double-blind, placebo-controlled study

Abstract: ObjectivesThe efficacy and safety of sifalimumab were assessed in a phase IIb, randomised, double-blind, placebo-controlled study (NCT01283139) of adults with moderate to severe active systemic lupus erythematosus (SLE).Methods431 patients were randomised and received monthly intravenous sifalimumab (200 mg, 600 mg or 1200 mg) or placebo in addition to standard-of-care medications. Patients were stratified by disease activity, interferon gene-signature test (high vs low based on the expression of four genes) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
275
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 434 publications
(289 citation statements)
references
References 34 publications
8
275
0
6
Order By: Relevance
“…The primary endpoint was not achieved in the phase-II trial of the anti-IFNα mAb, rontalizumab [79], whereas the primary endpoint (assessed at week 52) was achieved in the phase-IIb trial of a different anti-IFNα mAb, sifalimumab. In this latter trial, the absolute percentage difference in clinical response between patients treated with the highest dose of sifalimumab and those treated with placebo was 14% [80], similar to the absolute percentage differences observed in the successful trial with belimumab or tabalumab. Of note, however, were results from the phase-IIb trial of the anti-IFNα receptor mAb, anifrolumab, in which the absolute percentage difference in clinical response between patients treated with the optimal dose of anifrolumab and those treated with placebo being 26% [81].…”
Section: ) Targeting Of Baff Receptors Rather Than Of Baffsupporting
confidence: 52%
“…The primary endpoint was not achieved in the phase-II trial of the anti-IFNα mAb, rontalizumab [79], whereas the primary endpoint (assessed at week 52) was achieved in the phase-IIb trial of a different anti-IFNα mAb, sifalimumab. In this latter trial, the absolute percentage difference in clinical response between patients treated with the highest dose of sifalimumab and those treated with placebo was 14% [80], similar to the absolute percentage differences observed in the successful trial with belimumab or tabalumab. Of note, however, were results from the phase-IIb trial of the anti-IFNα receptor mAb, anifrolumab, in which the absolute percentage difference in clinical response between patients treated with the optimal dose of anifrolumab and those treated with placebo being 26% [81].…”
Section: ) Targeting Of Baff Receptors Rather Than Of Baffsupporting
confidence: 52%
“…Since the registration of our study, another randomized clinical trial using the CLASI score as an end point has been published (26). In patients with moderateto-severe skin disease (CLASI score $10), it was shown that 50% of patients had improvement in the CLASI activity score.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the development of several clinical interventions that include the use of antibodies to block IFNs and their downstream target genes to treat these autoimmune diseases (22). Emerging phase II/III clinical trial data suggest that these pathways can be inhibited therapeutically in an effective and safe manner (23,24). Should these agents continue to show a favorable safety profile, we believe that efforts should be made to move these interventions into the HIV cure arena.…”
Section: Discussionmentioning
confidence: 99%